2007
DOI: 10.1089/clo.2006.0059
|View full text |Cite
|
Sign up to set email alerts
|

Overcoming MIII Arrest from Spontaneous Activation in Cultured Rat Oocytes

Abstract: The rat oocyte spontaneously activates under a wide variety of conditions. This process progresses to MIII arrest that is not responsive to parthenogenetic activation and development. Insofar as activation involves extrusion of the second polar body (PBII), we set out to determine if preventing this step by inhibiting microfilaments would change the course of spontaneous activation (SA). In particular, how long does the effect of SA persist while retaining reversibility of PBII extrusion once inhibitors are re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
15
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 40 publications
1
15
0
Order By: Relevance
“…However, rat is an interesting model because the process of SEA is abortive [30] and aged eggs are arrested at M-III like stage [24]. The freshly ovulated eggs (14 h post-hCG surge) are less likely to undergo abortive SEA as compare to aged eggs in vivo [28,31,33].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, rat is an interesting model because the process of SEA is abortive [30] and aged eggs are arrested at M-III like stage [24]. The freshly ovulated eggs (14 h post-hCG surge) are less likely to undergo abortive SEA as compare to aged eggs in vivo [28,31,33].…”
Section: Discussionmentioning
confidence: 99%
“…Postovulatory aging-induced abortive SEA deteriorates the egg quality and limits assisted reproductive technologies (ART) such as in vitro fertilization (IVF), intra-cytoplasmic sperm injection (ICSI) and somatic cell nuclear transfer (SCNT) during animal cloning [14,[17][18][19]. Several drugs such as proteasome inhibitor, MG-135 [20,21], melatonin [22], verapamil [16] and pyruvate [23] have been used to prevent postovulatory aging-induced abortive SEA in vitro [16,24].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This prompted us to take a more detailed look into specifics of spontaneous activation. We found that spontaneous activation as measured by polar body (PB) extrusion times vary dramatically with ovular age of oocytes (Galat et al, 2007). For example, it is complete by 40 min in oocytes isolated 22 h post-hCG, whereas it lasts 1 h 30 min in oocytes isolated 18 h post-hCG and up to 3 h in oocytes isolated 14 h post-hCG.…”
Section: Lessons and Perspectives From Cloningmentioning
confidence: 98%
“…However, other groups had difficulties reproducing the achievement, perhaps because of inherited developmental toxicity and strain dependency of this particular drug (Mizumoto et al, 2008(Mizumoto et al, , 2010Nakajima et al, 2008;Tomioka et al, 2007;Webb et al, 2010). In search of alternatives, we discovered that the activation of rat oocytes could be reversibly suppressed with microtubule and microfilament disruptive agents such as cytochalasin B, cytochalasin D, nocodazole, and demecolcyne (Galat et al, 2007). Although the activation suppression was successful, these treatments decreased the parthenogenetic development as compared to controls.…”
Section: Lessons and Perspectives From Cloningmentioning
confidence: 99%